Paratransit Difa Bike as an Innovation of Economy Empowering and Accessibility for Difabel - Hutari, Riska Melinda (The Center for Disability Studies and Services Brawijaya University, 2019)
Difa Bike is one of the innovations in the field of transportation of Paratransit and a kind of online motorcycle taxi, but the difference is that both the driver and the customer are people with disabilities. In carrying out its services Difa Bike uses a lot of internet technology. Economic empowerment is the main objective of the establishment of Difa Bike so that people with disabilities are not entangled in the cycle of poverty. The accessibility aspect is also present in the service both for drivers and customers.